Proposed Business Strategy For Contemporary Rattan Furniture Company Case Study: Studi Hiji - Vania Griselda Pardede, Maria; Fachira, Ira (The Indonesian Journal of Business Administration, 2016)
Abstract. Furniture industry is one of potential industries that continue to grow along with development of property industry in Indonesia. Every year, the domestic demand for furniture products has increased in line with growth of property business. In 2015, it is projected to raise 15 percent and will continue to increase. Furniture market development in Indonesia is also supported by rising incomes of middle class economy especially those who live in urban areas. It gives big opportunity for Indonesia furniture manufacturer to cover domestic needs rather than just for exporting market. Studio Hiji is a Jakarta–based design studio that creates contemporary rattan furniture. Studio Hiji furnitures are designed by Mr.Abie abdillah, a reputable furniture designer who is known as one of the best rattan designer from Indonesia. Studio Hiji products had won several award and had been exhibited in International exhibition. Since beginning of 2014, Studio Hiji starts selling their furniture product such as chair, benches, stool, and tables. 90 percent of Studio Hiji furniture sales were bought by domestic market and there also small sales from buyer that came from South East Asia Region. Unfortunately, Studio Hiji company revenue has not given significant profit to the company compared to operational and marketing expense. Studio Hiji faced issue of having difficulty to expand their team and to hire new employee because of limited funds they had in this start up phase. Therefore, Studio Hiji need to have more effective and efficient marketing strategy. Acquiring new costumer to increase their sales is very important for Studio Hiji to increase their growth and sustainability in this industry.  Based on the research, it was found that Studio Hiji has two types of customer profiles and why the issue could be experienced by this company because Studio Hiji did not have specific marketing strategies for its customer profiles which has different characteristic. Therefore, there were discrepancies between the target market and how companies apply the marketing techniques and promotion tools to reach the target market. This problem can be solved by analyzing both internal and external factors to identify opportunities and threats of the industry as well as the strengths and weaknesses of the company. Internal and external analysis results are used to make SWOT – TOWS matrix which later is summarized in EFAS, IFAS, and SFAS analysis. This analysis will determine what strategic factor gives most influence on Studio Hiji Company.  Based on research and finding, Studio Hiji need to maximize their marketing effort and focus on B2B marketing strategy. By focusing marketing effort for B2B market, Studio Hiji can increase their sales and sustainability in its first phase. The research also includes a survey that is conducted to view general opinion and point of view of potential business company which is really important for arranging next marketing strategies. Output of the research is business solution based on internal and external business situational analysis which is strengthen by improving marketing mix. At last, author will describe the implementation of the business solution that is shown with schedule activities. Keywords : Furniture Design Industry, Business Strategy.  SWOT-TOWS analysis, EFAS, IFAS, and SFAS analysis, Improvement Marketing Mix.